Trademark right in domain name system: a jurisprudential analysis (2011)
Domain name system is a current development in the Internet as users increasingly establish their presence and accessibility. The Internet has created the much needed platform that transforms the world into a global village where people could relate and interact easily. It also offers producers and marketers a forum to advertise their goods and services without any limiting boundary. Welcome as this development is, it also raises the problem of the protection from infringement of business and product names that are registered and posted on the internet. Therefore, this article appraises the registration and implication of domain names on the internet as well as the jurisdictional challenges and legal means of protecting such names with a view to establishing a framework that ensures the adequacy of the law that regulates them.